The Implementation of Religious Tolerance and Moderation Values in Children's Character Building at Madrasah Ibtidaiyyah in Gorontalo, Indonesia - Supiah, Supiah; Wafi, Abdul; Ningsih, Syalwa (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
This study explores the implementation of Religious Moderation Tolerance values in shaping children's character at Madrasah Ibtidaiyyah Negeri 1 Kota Gorontalo, as well as the factors influencing its success. Using a qualitative approach, data were collected through in-depth interviews with teachers, students, and parents, classroom observations, and document analysis. The findings indicate tolerance and religious moderation values are implemented through curriculum integration, contextual learning approaches, and extracurricular activities. Success factors include the active role of teachers, parental support, and supportive madrasah policies. Challenges faced include a lack of understanding among some parents and socio-cultural challenges. This study concludes that education based on religious moderation tolerance effectively shapes children's character but requires synergy between schools, families, and the community to overcome obstacles. These findings are expected to serve as a reference for developing character education based on religious moderation values in other madrasahs.